An amphoteric reactivity of a mixed-valent bis(μ-oxo)dimanganese(iii, iv) complex acting as an electrophile and a nucleophile. Issue 1 (1st December 2015) - Sankaralingam, Muniyandi; Jeon, So Hyun; Lee, Yong-Min; Seo, Mi Sook; Ohkubo, Kei; Fukuzumi, Shunichi; Nam, Wonwoo
Abstract : A mixed-valent bis(μ-oxo)dimanganese(iii, iv ) complex showed an amphoteric reactivity in both electrophilic and nucleophilic oxidative reactions. Abstract : A mixed-valent bis(μ-oxo)dimanganese(iii, iv ) complex, [(dpaq)Mn III (O)2 Mn IV (dpaq)] + (1 ), was prepared by reacting a hydroxomanganese(iii ) complex, [(dpaq)Mn III (OH)] +, with hydrogen peroxide in the presence of triethylamine. The mixed-valent bis(μ-oxo)dimanganese(iii, iv ) complex (1 ) was well characterised by UV-vis, EPR and CSI-MS techniques. The electrophilic reactivity of1 was investigated in the oxidation of 2, 6-di- tert -butylphenol derivatives by1, in which the relative rate afforded a good Hammett correlation with a ρ value of −1.0. The nucleophilic character of1 was then investigated in aldehyde deformylation reactions, using 2-phenylpropionaldehyde (2-PPA) and benzaldehyde derivatives as substrates. In contrast to the case of the reaction of1 with 2, 6-di- tert -butylphenol derivatives, a positive ρ value of 0.89 was obtained in the Hammett plot, demonstrating that the bis(μ-oxo)-dimanganese(iii, iv ) complex is an active nucleophilic oxidant. Thus, 1 exhibited an amphoteric reactivity in both electrophilic and nucleophilic oxidative reactions.